9 practical node.js projects. (SitePoint Pty., 2018)
While there have been quite a few attempts to get JavaScript working as a server-side language, Node.js (frequently just called Node) has been the first environment that's gained any traction. It's now used by companies such as Netflix, Uber and Paypal to power their web apps. Node allows for blazingly fast performance; thanks to its event loop model, common tasks like network connection and database I/O can be executed very quickly indeed. In this book, we offer a selection of nine different practical projects that you can follow along with. It contains: Build a Simple Beginner App with Node, Bootstrap and MongoDB by James Hibbard How to Build a File Upload Form with Express and Dropzone.js by Lukas White How to Build and Structure a Node.js MVC Application by James Kolce User Authentication with the MEAN Stack by Simon Holmes and Jeremy Wilken Build a JavaScript Command Line Interface (CLI) with Node.js by Lukas White and Michael Wanyoike Building a Real-time Chat App with Sails.js by Michael Wanyoike Passport Authentication for Node.js Applications by Paul Orac Local Authentication Using Passport in Node.js by Paul Orac An Introduction to NodeBots by Patrick Catanzariti This book is for anyone who wants to start learning server-side development with Node.js. Familiarity with JavaScript is assumed.